Study protocol for a multi-session randomized sham-controlled trial of PCC- and amygdala-targeted neurofeedback for the treatment of PTSD - Lieberman, Jonathan M.; Lanius, Ruth A.; Théberge, Jean; Frey, Benicio N.; Frewen, Paul A.; Scharnowski, Frank; Steyrl, David; Ros, Tomas; Densmore, Maria; Tassinari, Emma; Matic, Vangel; Hosseini-Kamkar, Niki; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Post-traumatic stress disorder (PTSD) is marked by distressing and often chronic symptoms, including the reliving and re-experiencing of trauma memories, avoidance, negative alterations in cognition and mood, heightened arousal and reactivity, and dissociation. Current psychotherapies and pharmacotherapies may yield suboptimal results for many individuals with PTSD, underscoring the need for new approaches. Recent neuroimaging research highlights functional disruptions in brainstem, cerebellar, limbic, and cortical networks underlying PTSD. Real-time functional magnetic resonance imaging neurofeedback (rt-fMRI-NFB) is an emerging intervention that has directly targeted limbic (i.e., the amygdala) and cortical (i.e., the posterior cingulate [PCC]) regions and has shown promising initial findings in PTSD. However, key research gaps remain, such as the need for rigorous randomized controlled trials (RCTs) to establish clinical efficacy and neurophysiological specificity, determine optimal brain targets, and evaluate dose-response relationships. Methods This double-blind, multi-session RCT investigates whether targeting distinct brain regions via rt-fMRI-NFB yields differential therapeutic effects in individuals with PTSD (n = 72). Participants will be randomly assigned to PCC-targeted rt-fMRI-NFB, amygdala-targeted rt-fMRI-NFB, or a sham-control group. Each participant will complete three rt-fMRI-NFB sessions over three weeks, with clinical assessments at baseline, after each session, and at a one-month follow-up. The sham group will receive a ‘yoked’ feedback signal from a random participant in one of the experimental groups. The primary outcome is PTSD symptom severity, measured using the PTSD Checklist for DSM-5 (PCL-5). Secondary outcomes include depressive symptoms, emotion regulation difficulties, dissociation, anxiety, interoceptive awareness, sleep quality, and state PTSD symptoms during trauma provocation. Neural outcomes will also be examined, focusing on brain activation and connectivity patterns. Additionally, qualitative interviews and actigraphy will assess participants’ subjective experiences and track sleep and physical activity patterns. Discussion This trial aims to address critical research gaps by evaluating the therapeutic potential of rt-fMRI-NFB targeting the PCC and amygdala in PTSD. By employing a wide range of data collection methods, this study will provide valuable insights into the clinical and neural effects of rt-fMRI-NFB. This study will be the first to investigate the phenomenological dimension and physiological impacts of rt-fMRI-NFB in this population. Taken together, these findings are expected to contribute to the development of targeted neurofeedback interventions and clarify the therapeutic mechanisms underlying rt-fMRI-NFB for PTSD. Trial registration This study has been registered with ClinicalTrials.gov under the trial registration number NCT05456958. It was initially registered on July 13th, 2022, and most recently updated on October 9th, 2024.